1993
DOI: 10.1037/0735-7044.107.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Receptive field plasticity in the auditory cortex during frequency discrimination training: Selective retuning independent of task difficulty.

Abstract: Classical conditioning is known to induce frequency-specific receptive field (RF) plasticity in the auditory cortex (ACx). This study determined the effects of discrimination training on RFs at two levels of task difficulty. Single unit and cluster discharges were recorded in the ACx of adult guinea pigs trained in a tone-shock frequency discrimination paradigm (30 intermixed trials each of positive conditioned stimulus [CS+]-shock and negative CS [CS-] alone) with behavioral performance indexed by the cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
118
7

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(142 citation statements)
references
References 35 publications
17
118
7
Order By: Relevance
“…The lack of plasticity in the STD group might seem inconsistent with prior findings of specific A1 plasticity in both classical (Bakin & Weinberger, 1990;Edeline & Weinberger, 1993;Gonzalez-Lima & Scheich, 1986b;Ohl & Scheich, 1996) and instrumental avoidance (Bakin et al, 1996) fear conditioning. Fear conditioning studies have concentrated on changes in receptive field tuning and have not studied possible modifications in threshold or bandwidth.…”
Section: Auditory Learning Without Auditory Cortical Plasticitycontrasting
confidence: 91%
“…The lack of plasticity in the STD group might seem inconsistent with prior findings of specific A1 plasticity in both classical (Bakin & Weinberger, 1990;Edeline & Weinberger, 1993;Gonzalez-Lima & Scheich, 1986b;Ohl & Scheich, 1996) and instrumental avoidance (Bakin et al, 1996) fear conditioning. Fear conditioning studies have concentrated on changes in receptive field tuning and have not studied possible modifications in threshold or bandwidth.…”
Section: Auditory Learning Without Auditory Cortical Plasticitycontrasting
confidence: 91%
“…Thus, taken together, the ECM influences short-and longterm plasticity of synapses and thereby potentially regulates signal processing within a neuronal network during learning. Indeed, auditory associative learning has been correlated with structural changes of topographic connections within primary ACx (19,(29)(30)(31), changes in interneuron activity (32,33), and Ca 2+ -dependent synaptic processing (34). However, further work will have to investigate the exact cellular and network effects of ECM removal in sensory cortex during learning processes in vivo.…”
Section: Potential Cellular Mechanisms Of Ecm-derived Modulation Ofmentioning
confidence: 99%
“…Though a previous study (Sakurai, 1990b) has shown that neurons in AC are involved in sensory discrimination and retention for WM, the present study indicates that AC neurons are involved in those processes not only for WM but also for RM. These functions of AC could be predicted from learning-induced changes of activity of AC neurons (Edeline et al, 1990) and learning-induced plasticity of receptive fields in AC (Weinberger et al, 1990;Edeline and Weinberger, 1993). Especially with regard to retention by AC neurons, the posttone facilitation of activity of AC units during the sequential presentation of tones (McKenna et al, 1989) might be related to a mechanism underlying the retention.…”
Section: Unique Functions Of the Auditory Cortexmentioning
confidence: 99%
“…These responses are surely taskperformance dependent, because the neurons showed no specific responses to the tones at times when there was no memory task. A recent study showing receptive field plasticity in the AC during frequency discrimination training (Edeline and Weinberger, 1993) also indicates the flexibility of AC neurons for learned task performance.…”
Section: Unique Functions Of the Auditory Cortexmentioning
confidence: 99%